Creating and Implementation Elective Courses at Higher Education Institution - Experience Analysis - Hahele, Rudite (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Rīga StradiņšUniversity (RSU) Internal Rules of Studies No 1 stipulate that alongside thecompulsory study courses, students must choose a number of elective courses inall six years of their studies. A considerable part of medical studentsare planning to work as general practitioners. Current trends in the societyand health care allow to conclude that more and more patients wish to usenatural remedies therefore family doctors must possess good knowledge in thisfield. The staff of the Department ofBiology and Microbiology offers an innovative study course „Medicinal Plantsand Their Use”. The course must correspond to the highest quality standards inorder to be chosen by the students. Thearticle summarizes the experience in developing the course, as well as analysesits implementation, evaluation and perfection.